A prospective study on the use of magnesium sulfate in prevention and management of eclampsia with emphasis on adverse drug reactions - Shah, Heena; Sattigeri, B. M.; Brahmbhatt, Shruti; Singh, Parul; Parikh, Devang; Kumar, Ashok (International Journal of Research in Medical Sciences, 2017)
Introduction: The hypertensive disorders in pregnancy are the leading causes of maternal and perinatal mortality. Management of preeclampsia and eclampsia remains controversial even today. Several drugs with different regimens are available at present. As a consequence; women are treated in various ways by different regimens. Aim: Our work aimed to study the use of various magnesium sulfate regimens used in management of eclampsia in a tertiary care teaching rural hospital. Methods: A prospective, observational, non-interventional study was carried out among the eclamptic patients admitted to obstetrics ward. After explaining the purpose and method of study, through the patient information sheet, patients willing to sign the informed consent form were enrolled for the study. Relevant data was gathered from their case files and by direct interview with the patients that were recorded in the case record form. Results: Of the 35 cases of eclampsia recorded during the study period, we observed that all the patients were treated with Pritchard’s regimen of Magnesium Sulfate. It was noticed that there was improvement in all the patients with no adverse drug reactions recorded during the time of management. Conclusion: Maternal and perinatal mortality can be reduced to major extent by prevention of eclampsia. Prompt diagnosis and institution of therapy by selecting an ideal anticonvulsant is essential as the maternal and perinatal mortality progressively rises with increase no of convulsions. Magnesium Sulfate is a potent anticonvulsant with mild antihypertensive activity with less adverse effects.